Analysis of Chemical Reaction Kinetics Behavior of Nitrogen Oxide During Air-staged Combustion in Pulverized Boiler - Jun-Xia Zhang; Jiang Feng Zhang (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Because the air-staged combustion technology is one of the key technologies with low investment running costs and high emission reduction efficiency for the pulverized boiler, it is important to reveal the chemical reaction kinetics mechanism for developing various technologies of nitrogen oxide reduction emissions. At the present work, a three-dimensional mesh model of the large-scale four corner tangentially fired boiler furnace is established with the GAMBIT pre-processing of the FLUENT software. The partial turbulent premixed and diffusion flame was simulated for the air-staged combustion processing. Parameters distributions for the air-staged and no the air-staged were obtained, including in-furnace flow field, temperature field and nitrogen oxide concentration field. The results show that the air-staged has more regular velocity field, higher velocity of flue gas, higher turbulence intensity and more uniform temperature of flue gas. In addition, a lower negative pressure zone and lower O2 concentration zone is formed in the main combustion zone, which is conducive to the NO of fuel type reduced to N2, enhanced the effect of NOx reduction.